Comparison of Learning Outcomes Between Discovery Learning with Inquiry Learning Reviewed of Student Learning Independence At Vocational High School - Lukitasari, Febriani; Nurlaela, Luthfiyah; Ismawati, Rita; Rijanto, Tri (Universitas Malikussaleh, 2020)
The provision of education provides a positive value for the development of the quality of Human Resources (HR), because global challenges and competition between nations in various aspects of life are increasingly competitive. This study aims to find the effect of learning models find the effect of discovery learning learning models with inquiry learning learning models to increase student learning outcomes; find the effect of student learning independence on student learning outcomes; and find interactions between discovery learning, inquiry learning and student learning independence models on student learning outcomes.This type of research is a quasi-experimental study, which is to examine student learning outcomes in food knowledge subjects using discovery learning and inquiry learning models. The research design used in this study is factorial design. Data collection techniques were carried out by observation and tests. Instrument of student learning outcomes. This study concludes that: (1) there is a significant difference in the effect of discovery learning models compared to inquiry learning models on improving student learning outcomes; (2) there is a significantly higher difference in high learning independence compared to students with low learning independence on student learning outcomes, and (3) there is an interaction between discovery learning, inquiry learning and student learning independence towards student learning outcomes. Based on the above conclusions as a whole shows there are differences in the application of learning models, the level of independence and interaction between the use of learning models, and the level of independence of student learning outcomes.